Characterization of Bacillus amyloliquefaciens BA-4 and its biocontrol potential against Fusarium-related apple replant disease - Li, Bo; He, Xiaoxing; Guo, Saiya; Li, Dongxu; Wang, Yanan; Meng, Xianglong; Dai, Pengbo; Hu, Tongle; Cao, Keqiang; Wang, Shutong (Frontiers in Plant Science, 2024)
Apple replant disease (ARD), caused by Fusarium pathogens, is a formidable threat to the renewal of apple varieties in China, necessitating the development of effective and sustainable control strategies.In this study, the bacterial strain BA-4 was isolated from the rhizosphere soil of healthy apple trees in a replanted orchard, demonstrating a broad-spectrum antifungal activity against five crucial apple fungal pathogens. Based on its morphology, physiological and biochemical traits, utilization of carbon sources, and Gram stain, strain BA-4 was tentatively identified as Bacillus amyloliquefaciens.Phylogenetic analysis using 16S rDNA and gyrB genes conclusively identified BA-4 as B.amyloliquefaciens. In-depth investigations into B. amyloliquefaciens BA-4 revealed that the strain possesses the capacity to could secrete cell wall degrading enzymes (protease and cellulase), produce molecules analogous to indole-3-acetic acid (IAA) and siderophores, and solubilize phosphorus and potassium. The diverse attributes observed in B. amyloliquefaciens BA-4 underscore its potential as a versatile microorganism with multifaceted benefits for both plant well-being and soil fertility. The extracellular metabolites produced by BA-4 displayed a robust inhibitory effect on Fusarium hyphal growth and spore germination, inducing irregular swelling, atrophy, and abnormal branching of fungal hyphae. In greenhouse experiments, BA-4 markedly reduced the disease index of Fusariumrelated ARD, exhibiting protective and therapeutic efficiencies exceeding 80% and 50%, respectively.Moreover, BA-4 demonstrated plant-promoting abilities on both bean and Malus robusta Rehd. (MR) seedlings, leading to increased plant height and primary root length. Field experiments further validated the biocontrol effectiveness of BA-4, demonstrating its ability to mitigate ARD symptoms in MR seedlings with a notable 33.34% reduction in mortality rate and improved biomass.Additionally, BA-4 demonstrates robust and stable colonization capabilities in apple rhizosphere soil, particularly within the 10-20 cm soil layer, which indicates that it has long-term effectiveness potential in field conditions. Overall, B. amyloliquefaciens BA-4 emerges as a promising biocontrol agent with broad-spectrum antagonistic capabilities, positive effects on plant growth, and strong colonization abilities for the sustainable management of ARD in apple cultivation.